DOI: 10.11606/d.6.2010.tde-13072010-112932
|View full text |Cite
|
Sign up to set email alerts
|

Tabagismo e transtorno mental comum na população de São Paulo - SP: um estudo a partir do inquérito de saúde no município de São Paulo (ISA-CAPITAL)

Abstract: AGRADECIMENTOSMuitos foram os que colaboraram, direta ou indiretamente, para a realização deste trabalho, indicando e sugerindo caminhos, amenizando momentos difíceis, apoiando decisões importantes, enfim, tornando-o possível. A todos minha eterna gratidão, e em especial gostaria de agradecer:Ao Prof. Dr. Antonio Augusto Pinto Junior, que me ensinou a paixão pela pesquisa e me incentivou a seguir na carreira acadêmica.Ao Prof. Dr. Chester Luís Galvão Cesar, que acreditou em mim permitindo meu ingresso à Pós Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…(LUDERMIR, 2008) Individuals who had never studied or had a small number of studies, up to three years, had a higher prevalence of CMD, while individuals aged 12 years and over of studies had a prevalence of three times lower. (MEDEIROS, 2010) Exposure to factors such as feeling insecure and lack of hope, and rapid social changes explain the greater vulnerability of individuals with low socioeconomic levels and schooling. (FRYERS et al, 2005) Regarding alcohol intake and tobacco use, this research corroborates similar findings in the literature, where it was found that more than half avoid it.…”
Section: Discussionmentioning
confidence: 99%
“…(LUDERMIR, 2008) Individuals who had never studied or had a small number of studies, up to three years, had a higher prevalence of CMD, while individuals aged 12 years and over of studies had a prevalence of three times lower. (MEDEIROS, 2010) Exposure to factors such as feeling insecure and lack of hope, and rapid social changes explain the greater vulnerability of individuals with low socioeconomic levels and schooling. (FRYERS et al, 2005) Regarding alcohol intake and tobacco use, this research corroborates similar findings in the literature, where it was found that more than half avoid it.…”
Section: Discussionmentioning
confidence: 99%
“…(LUDERMIR, 2008) Individuals who had never studied or had a small number of studies, up to three years, had a higher prevalence of CMD, while individuals aged 12 years and over of studies had a prevalence of three times lower. (MEDEIROS, 2010) Exposure to factors such as feeling insecure and lack of hope, and rapid social changes explain the greater vulnerability of individuals with low socioeconomic levels and schooling. (FRYERS et al, 2005) Regarding alcohol intake and tobacco use, this research corroborates similar findings in the literature, where it was found that more than half avoid it.…”
Section: )mentioning
confidence: 99%
“…1 Tobacco consumption is currently considered a chemical addiction that exposes individuals to several toxic substances, and it has been included in the category of mental and behavioral disorders due to psychoactive substance use of the International Classification of Diseases, Tenth Revision (ICD-10), issued by the World Health Organization (WHO). 2,3 The economic and societal costs associated with smoking are also high, and are estimated to reach US$ 1 trillion by the 2030s. 4 In 2002, there were one billion male and 250 million female smokers in the world, with significantly higher prevalence rates, in both sexes, in middle-to low-income countries when compared with high-income countries.…”
Section: Introductionmentioning
confidence: 99%